9-8•{7-n•[5-4•(3-2•1)]}=1
Răspunsuri la întrebare
Răspuns de
1
9-8•[7-n•(5-4•1)]=1
9-8•(7-n•1)=1
9-8•(7-n)=1
-8•(7-n)=1-9
-8•7+8n=-10
-56+8n=-10
8n=-10+56
8n=46
n=46/8
n=6
9-8•(7-n•1)=1
9-8•(7-n)=1
-8•(7-n)=1-9
-8•7+8n=-10
-56+8n=-10
8n=-10+56
8n=46
n=46/8
n=6
sara550:
Am greșit ceva. Scuze
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Informatică,
9 ani în urmă
Engleza,
9 ani în urmă
Engleza,
9 ani în urmă